2022
DOI: 10.31083/j.ceog4906124
|View full text |Cite
|
Sign up to set email alerts
|

Charité Caesarean Birth Improves Birth Experience in Planned and Unplanned Caesarean Sections While Maintaining Maternal and Neonatal Safety: A Prospective Cohort Study

Abstract: Background: In this study, we aimed to assess the safety of a modified caesarean delivery (Charité caesarean birth) in an extended frame of indications, and to examine its impact on parents' birth experience and long-term effects. Methods: This prospective cohort study was performed from January to June 2019. A standardized questionnaire was given to all women who gave birth as an inpatient delivery. Eight months after hospital discharge, all women who gave consent were sent a follow-up questionnaire including… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
2
0
0
Order By: Relevance
“…The results of this study are consistent with those of earlier research and case studies, which found no differences in maternal outcomes and the majority of newborn outcomes [2,[4][5][6][7]. According to [18], there was no significant difference between Charité and traditional caesarean birth groups in terms of infant hospitalization rates, umbilical cord parameters, maternal blood loss, or operation time. Women who had a Charité caesarean delivery were substantially happier with their birthing experience than those who had a standard caesarean delivery.…”
Section: Discussionsupporting
confidence: 90%
“…The results of this study are consistent with those of earlier research and case studies, which found no differences in maternal outcomes and the majority of newborn outcomes [2,[4][5][6][7]. According to [18], there was no significant difference between Charité and traditional caesarean birth groups in terms of infant hospitalization rates, umbilical cord parameters, maternal blood loss, or operation time. Women who had a Charité caesarean delivery were substantially happier with their birthing experience than those who had a standard caesarean delivery.…”
Section: Discussionsupporting
confidence: 90%
“…Women’s health-related quality-of-life might also be affected by the type of procedure performed (for example, the Charité cesarean birth or “family-centered cesarean”), as well as possible surgical complications. These aspects have also been highlighted in other studies [ 4 , 11 , 20 , 21 ].…”
Section: Discussionsupporting
confidence: 73%